Impact of weather on the risk of surgical site infections in a tropical area - Fortaleza, Carlos Magno Castelo Branco [UNESP]; Silva, Marina de Oliveira [UNESP]; Saad Rodrigues, Fernanda [UNESP]; da Cunha, Antônio Ribeiro [UNESP] (Elsevier, 2019)
We studied the impact of average daily temperature and relative humidity on the risk of surgical site infections in 36,429 surgeries performed in a hospital in inner Brazil. Adjusted Poisson regression models found an association between surgical site infections and temperature (rate ratio [RR], 1.013; 95% confidence interval [CI], 1.001-1.025). The effect was concentrated on clean wound procedures and was greater over the 75th (RR, 1.109; 95% CI, 1.015-1.212) and 90th (RR, 1.196; 95% CI, 1.055-1.355) percentiles of daily temperature.
Keywords: Surgical site infections; Tropical area; Weather